Loss of the translational repressor 4E-BP1 promotes skin carcinogenesis - Zhou, Yibin; Dou, Hanyu; Liu, Yifeng; Wang, Juan; Ding, Xiaolei; Huang, Taomin (Frontiers in Pharmacology, 2026)
IntroductionSkin squamous cell carcinoma (SCC) arises from dysregulated epidermal homeostasis characterized by aberrant keratinocyte proliferation and pathological angiogenesis. The eukaryotic translation initiation factor 4E‐binding protein 1 (4E‐BP1) functions as a critical suppressor of cap-dependent translation by interacting with eIF4E, thereby constraining protein synthesis and cell growth. However, its role in SCC remains elusive.MethodsTo address the role of 4E‐BP1 function in SCC pathogenesis, we employed a two‐stage chemical carcinogenesis model in 4E‐BP1‐deficient mice.Results4E‐BP1‐deficient mice exhibited a significantly increased papilloma burden compared to wild-type controls, accompanied by enhanced keratinocyte proliferation and augmented tumor vascularization. Analysis of human SCC specimens revealed elevated 4E‐BP1 phosphorylation together with increased proliferative and angiogenic markers and activation of the mTOR signaling pathway, mirroring molecular features observed in 4E‐BP1‐deficient tumors.DiscussionCollectively, these findings establish 4E‐BP1 as a tumor suppressor in skin carcinogenesis that constrains both proliferative and angiogenic processes, underscoring the contribution of dysregulated translation to SCC development.